CHARACTERIZATION AND ANTIMICROBIAL ACTIVITIES OF CINCHONA (CINCHONA LEDGERIANA MOENS EX TRIMEN) HONEY AS ACTIVE SUBSTANCE CANDIDATE FOR ANTIACNE - Andam Dewi, Mira
Currently, many studies have reported the therapeutic properties of honey, including manuka honey whose activity has been confirmed against about 60 types of bacteria, including aerobic and anaerobic, as well as Gram positive and negative. Manuka honey has been reported to be effective in treating skin infections that are resistant to antibiotics and gastrointestinal disorders and is recognized as having a role and potential as a topical active ingredient for post-surgical treatment or wound infection. Besides being consumed, manuka honey is often used as a mask to moisturize the skin and relieve acne inflammation. This fact has encouraged research to test and prove the antimicrobial effect of other types of honey that are specific, such as manuka honey. A recently published research report on honey disseminates the importance of continued research activities to encourage new findings on the benefits and uses of honey as a functional food and medical application. In line with this, this study carried out the characterization and antimicrobial activity test of cinchona (Cinchona ledgeriana Moens ex Trimen) honey as a candidate substance for antiacne.